Plasma membrane microdomains regulate turnover of transport proteins in yeast - Großmann, Guido (The journal of cell biology, 2008)
In this study, we investigate whether the stable segregation of proteins and lipids within the yeast plasma membrane serves a particular biological function. We show that 21 proteins cluster within or associate with the ergosterol-rich membrane compartment of Can1 (MCC). However, proteins of the endocytic machinery are excluded from MCC. In a screen, we identified 28 genes affecting MCC appearance and found that genes involved in lipid biosynthesis and vesicle transport are significantly overrepresented. Deletion of Pil1, a component of eisosomes, or of Nce102, an integral membrane protein of MCC, results in the dissipation of all MCC markers. These deletion mutants also show accelerated endocytosis of MCC-resident permeases Can1 and Fur4. Our data suggest that release from MCC makes these proteins accessible to the endocytic machinery. Addition of arginine to wild-type cells leads to a similar redistribution and increased turnover of Can1. Thus, MCC represents a protective area within the plasma membrane to control turnover of transport proteins.